ON THE MOTIVIC SPECTRAL SEQUENCE. (25th November 2015) - Garkusha, Grigory; Panin, Ivan
Abstract : It is shown that the Grayson tower for K -theory of smooth algebraic varieties is isomorphic to the slice tower of S^1 -spectra. We also extend the Grayson tower to bispectra, and show that the Grayson motivic spectral sequence is isomorphic to the motivic spectral sequence produced by the Voevodsky slice tower for the motivic K -theory spectrum KGL . This solves Suslin's problem about these two spectral sequences in the affirmative.